DINAMIKA AGAMA HINGGA NORMA BARU MASYARAKAT DI TENGAH PANDEMIK COVID-19 (Studi Kasus Masyarakat Desa Ploso Ngawi) - Alma'a Cinthya Hadi (Religi: Jurnal Studi Agama-agama, 2020)
Pagebluk or epidemic that we are currently experiencing, namely the corona virus that entered Indonesia since March 2020 has claimed more than 28.233 case of the Indonesian population and has claimed the work of both workers and employees due to Termination of Employment (PHK) due to stalled economic flows both local and global, but it does not stop here because the numbers continue to soar. Not only that a variety of significant implications occur in terms of religion and culture. This paper discusses the role of religion in the community of Ploso village in Ngawi district response to the Covid-19 pandemic, the substance that makes it form and changing occur in society.